2020
DOI: 10.5530/jppcm.2019.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction a Global Concern: A Cross-Sectional Appraisal amongst Imminent Medical Doctors of National Defence University of Malaysia

Abstract: Background: Recent evolution in terms of technology and availability of the internet has brought several innovations that made work and access to information straightforward. Nonetheless, the danger of pathological internet addiction and its adverse consequences are frightening. Objectives: The primary goal of this research is to determine the level of internet addiction among undergraduate medical students at National Defence University, Malaysia. Methods: A structured questionnaire comprising of section A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…These findings are consistent with the findings of earlier studies that reported a similar pattern. (1,14,15) Lastly, it has been found that students residing in the hostel had the highest mean internet addiction score compared with day scholars. These findings are consistent with the findings of Qadir et al (23) This can also be explained as students residing in hostels, being alone, get bored and spend longer duration using the internet for change of mind.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These findings are consistent with the findings of earlier studies that reported a similar pattern. (1,14,15) Lastly, it has been found that students residing in the hostel had the highest mean internet addiction score compared with day scholars. These findings are consistent with the findings of Qadir et al (23) This can also be explained as students residing in hostels, being alone, get bored and spend longer duration using the internet for change of mind.…”
Section: Discussionmentioning
confidence: 98%
“…The world has transformed over recent years in the field of technology while the availability of the internet is one of the major contributory factors to this milestone. (1) The number of people using the internet worldwide is growing exponentially; the current report indicated that more than 4 billion people are using the internet globally. As such, over half of the world's population is now online, with about a quarter of a billion new users recorded for the first time in 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation